(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article explores effective assessment techniques tailored for English Language Learners (ELLs). Traditional testing methods often fail to capture the full range of skills and knowledge that ELLs possess due to language barriers, cultural gaps, and unfamiliar formats. The paper presents a variety of inclusive and formative assessment strategies, such as portfolio-based assessment, peer review, performance tasks, and scaffolding in test instructions. Practical classroom-based examples demonstrate how these approaches provide a more accurate reflection of ELLs’ abilities while also promoting motivation and learner autonomy. The article argues that equitable assessment is not just a technical concern but a cornerstone of inclusive education.